The first member of the eleven-vertex azadicarbaborane series, 1,6,9-NC2B8H13, and its N-alkyl derivatives - Janousek, Zbynek; Dostál, Radim; Machácek, Jan; Hnyk, Drahomír; Stíbr, Bohumil (Dalton transactions (Cambridge, England, 2006)
Reactions between closo-1,2-C(2)B(8)H(10) (1) and amines of general formulation R(1)R(2)NH (where R(1), R(2) = H, H; Me, H; t-Bu, H and Et, Et) resulted in a straightforward cluster expansion and formation of the 11-vertex arachno-azadicarbaboranes of the 1,1-R(1),R(2-)1,6,9-NC(2)B(8)H(11) (2) cluster constitution (where R(1), R(2) = H, H 2a; Me, H 2b; t-Bu, H 2c and Et, Et 2d) in yields 10-75%, depending on the nature of the amine used. The reactions are the first example of a direct closo to arachno transformation in the area of cluster-boron compounds. Compounds 2b and 2c were isolated in two isomeric forms anti- and syn- that differ in the positioning of the t-Bu substituent with respect to the bridging hydrogen site. Deprotonation of compounds 2 generally leads to removal of the bridging proton and formation of the [1,1-R(1),R(2-)1,6,9-NC(2)B(8)H(11)](-) (2-) anions that, in the case of the monoalkylated Me and t-Bu derivatives, adopt only an anti configuration. The structure of anti-2c was determined by X-ray diffraction analysis and the geometries of the parent compound and the corresponding syn and anti isomers were optimised at the RMP2/6-31G* level. The composition of all compounds is consistent with the results of mass spectrometry and multinuclear ((1)H and (11)B) spectroscopy complemented by two-dimensional [(11)B-(11)B]-COSY and (1)H{(11)B(selective)} NMR measurements. Experimental (11)B chemical shifts generally show acceptable agreement with theoretical values calculated by GIAO methods, in particular at GIAO-MP2/II, where possible.